Facing the facts: The Runx2 gene is associated with variation in facial morphology in primates. Issue 111 (October 2017) - Ritzman, Terrence B.; Banovich, Nicholas; Buss, Kaitlin P.; Guida, Jennifer; Rubel, Meagan A.; Pinney, Jennifer; Khang, Bao; Ravosa, Matthew J.; Stone, Anne C.
Abstract: The phylogenetic and adaptive factors that cause variation in primate facial form—including differences among the major primate clades and variation related to feeding and/or social behavior—are relatively well understood. However, comparatively little is known about the genetic mechanisms that underlie diversity in facial form in primates. Because it is essential for osteoblastic differentiation and skeletal development, the runt-related transcription factor 2 ( Runx2 ) is one gene that may play a role in these genetic mechanisms. Specifically, polymorphisms in the QA ratio (determined by the ratio of the number of polyglutamines to polyalanines in one functional domain of Runx2 ) have been shown to be correlated with variation in facial length and orientation in other mammal groups. However, to date, the relationship between variation in this gene and variation in facial form in primates has not been explicitly tested. To test the hypothesis that the QA ratio is correlated with facial form in primates, the current study quantified the QA ratio, facial length, and facial angle in a sample of 33 primate species and tested for correlation using phylogenetic generalized least squares. The results indicate that the QA ratio of the Runx2 gene is positively correlated with variation in relative facial length in anthropoid primates. However, no correlation was found in strepsirrhines, and there was no correlation between facial angle and the QA ratio in any groups. These results suggest that, in primates, the QA ratio of the Runx2 gene may play a role in modulating facial size, but not facial orientation. This study therefore provides important clues about the genetic and developmental mechanisms that may underlie variation in facial form in primates.